EVALUASI PENGELOLAAN KEUANGAN PEMERINTAH DAERAH KOTA SEMARANG - Rona Yunita Nugraheni; Zainal Hidayat (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The background of this research is to management that the city government budget from 26 the obligatory affair and 7 affairs option but 4 of 26 the obligatory affair and 1 of 7 affairs option is not in accordance with what has been previously budgeted. This caused SiLPA to appear on 2011-2015 and thus affect the process of qualified opinion (WDP) from BPK. This research uses to evaluation the management city government budget comparing between budget and realization, and finds some factor. Research theory from Lester and Steward, where one of the tasks of evaluation is to assess the success or failure of a policy based on the predefined standards or criteria. The method uses mixed method and combines qualitative description with quantitative descriptive statistics. Information for this research was gathered using purposive sampling technique from Financial Management Agency and Regional Assets (BPKAD) and the Autonomous Region of Semarang City. The result of this research stated that out of 26 compulsory work and 7 optional works, there are some compulsory works whose percentage of budget realization is below the average number and that includes these categories: education; public works; spatial planning; regional autonomy of general administration of regional financial administration, regional apparatus, staffing and coding; ESDM works (Ministry of Energy and Mineral Resources). There are several factors that influence the discrepancy between budget and realization in the compulsory and optional works of public policy, emergency response, regional regulations and political interests.